Penyimpangan Maksim Kesopanan Dalam Video “Mbambong” Di Youtube Woko Channel - Alifia Risnadian Aulia; Wendy Febia Nuricahyati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Deviations from the principles of politeness by speech participants are generally due to the desire to achieve a speech. The implicit meaning of speech can have a positive or negative meaning, depending on the context and circumstances when the speech occurs. The purpose of this deviation is, for example, to ridicule, humiliate, show antipathy, and so on, the purpose of which is to harm other people. This research is entitled Deviations from the Maxim of Politeness in the "Mbambong" Video on the Youtube Woko Channel. This research will discuss the forms of deviation from the maxim of politeness in the video "Mbambong" on the Woko Channel YouTube. The aim of this research is to understand the forms of deviation from the maxim of politeness in the "Mbambong" video on the Woko Channel YouTube. This research includes pragmatic studies. The theory used in this research is Leech's maxim of politeness theory because it is considered the most complete of the existing parts of the maxim of politeness. This study used qualitative research methods. Dhata in this research was taken from conversations between paraga in the video "Mbambong" on the Woko Channel YouTube. The source of dhata in this research comes from videos and then transcribed in the form of words and sentences. Based on the results of the research, there are 6 deviations from the maxims in the "Mbambong" video, namely deviations from the maxims: wisdom, generosity, praise, humility, compatibility and sympathy.